Think Again : Contrarian Reflections on Life, Culture, Politics, Religion, Law, and Education - Fish, Stanley Eugene (Book collections on Project MUSE., 2015)
From 1995 to 2013, Stanley Fish's provocative New York Times columns consistently generated passionate discussion and debate. In Think Again, he has assembled almost one hundred of his best columns into a thematically arranged collection with a substantial new introduction that explains his intention in writing these pieces and offers an analysis of why they provoked so much reaction.Some readers reported being frustrated when they couldn't figure out where Fish, one of America's most influential thinkers, stood on the controversies he addressed in the essays-from atheism and affirmative action to plagiarism and postmodernism. But, as Fish says, that is the point. Opinions are cheap; you can get them anywhere. Instead of offering just another set of them, Fish analyzes and dissects the arguments put forth by different sides-in debates over free speech, identity politics, the gun lobby, and other hot-button topics-in order to explain how their arguments work or don't work. In short, these are essays that teach you not what to think but how to think more clearly.Brief and accessible yet challenging, these essays provide all the hard-edged intellectual, cultural, and political analysis one expects from Fish. At the same time, the collection includes a number of revealing and even poignant autobiographical essays in which, as Fish says, "readers will learn about my anxieties, my aspirations, my eccentricities, my foibles, my father, and my obsessions-Frank Sinatra, Ted Williams, basketball, and Jews." Reflecting the wide-ranging interests of one of today's leading critics, this is Fish's broadest and most engaging book to date.